1982
DOI: 10.1042/bj2080221
|View full text |Cite
|
Sign up to set email alerts
|

The effects of glucagon, phenylephrine and insulin on the phosphorylation of cytoplasmic, mitochondrial and membrane-bound proteins of intact liver cells from starved rats

Abstract: 1. The effects of glucagon, insulin and phenylephrine on the phosphorylation of cytoplasmic, mitochondrial and membrane proteins were studied in intact hepatocytes from 24 h-starved rats incubated with [32P]Pi. A rapid cell-fractionation technique was used, followed by radioautography of the proteins separated by sodium dodecyl sulphate/polyacrylamide-gel electrophoresis. 2. Glucagon consistently caused a significant increase in the phosphorylation of four readily separable cytoplasmic phosphoproteins, of Mr 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

1985
1985
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 45 publications
0
29
1
Order By: Relevance
“…4, lane b) and forskolin (Fig. 4, lane c) stimulated the phosphorylation of various proteins in isolated rat hepatocytes, among them a weakly phosphorylated 23-kDa protein which is most likely the phosphoprotein described by Vargas et al [53]. We were, however, unable to detect under these conditions a phosphoprotein with the same apparent molecular size as protein 111.…”
Section: Effect Of Glucagon and Forskolin On The Phosphorylation Of Lcontrasting
confidence: 40%
See 2 more Smart Citations
“…4, lane b) and forskolin (Fig. 4, lane c) stimulated the phosphorylation of various proteins in isolated rat hepatocytes, among them a weakly phosphorylated 23-kDa protein which is most likely the phosphoprotein described by Vargas et al [53]. We were, however, unable to detect under these conditions a phosphoprotein with the same apparent molecular size as protein 111.…”
Section: Effect Of Glucagon and Forskolin On The Phosphorylation Of Lcontrasting
confidence: 40%
“…phospholamban) [13 -191, platelets [26 -451, liver [53], adrenal cortex [63,64], adipocytes [65,66], granulocytes [67], Leydig tumor cells [69], bovine lens [70, 711 and in 3T3 cells [72]. However, in most cases the possible identity of these proteins has not been explored.…”
Section: Comparison Of the Tryptic Phosphopeptides F R O M Protein 11mentioning
confidence: 99%
See 1 more Smart Citation
“…When isolated rat liver mitochondria were incubated with g 32 P-ATP, phosphoproteins of 32 and 42 kDa were detected and identified as two different forms of succinyl-CoA synthetase [7]. Additionally, a 35-kDa mitochondrial protein was shown to be phosphorylated in rat hepatocytes in response to glucagon; the identity of the mitochondrial protein kinase responsible for the phosphorylation of the 35-kDa protein, however, was not known [8]. These studies showed that mitochondria contained enzymes capable of catalysing protein phosphorylation.…”
Section: Phosphorylation Of Mitochondrial Proteinsmentioning
confidence: 96%
“…Glucacon also stimulates phosphorylation of mitochondrial proteins in vivo [4] or in isolated cell preparations [5]. CAMP itself seems to affect mitochondrial processes [6], and CAMP binding proteins have been detected in mitochondria [7,8].…”
Section: Introductionmentioning
confidence: 99%